Community service physiotherapists - what do they know about hiv/aids? - A. Mangrey; L. Naidoo; T. Naidoo; T. Puckree (AOSIS, 2010)
Southern Africa  has  been  identified  as  the  heart  of  the  HIV/AIDS pandemic for more than two decades. At its heart lies KwaZulu Natal  with  more  than  a  third  of  its  ten  million  inhabitants  infected.  In  its effort  to  ensure  service  to  all,  the  South  African  National  Department  of Health  has  instituted  several  strategies  to  ensure  some  service  delivery to the rural and urban poor communities. One of these strategies was the introduction of community service in 2002, for physiotherapists and other health  care  professionals  for  one  year  following  successful  completion  of the University degree. In keeping with this, Physiotherapy curricula had to change with the changing needs of the increased demands placed on the new graduates. This study undertook to find out the knowledge, attitudes and experience of the 2004 community service physiotherapists in KwaZulu Natal with regard to HIV/AIDS in their community service year. Seventy-seven community service physiotherapists who serviced KwaZulu  Natal  in  2004  participated.  Of  the  59  contactable  subjects,  47  returned  their  questionnaires  and  only  44 were viable for analysis. The results showed that 100% of the participants had contact with HIV/AIDS patients during  their  community  service  year.  These  therapists  felt  that  a  physiotherapist  can  play  a  vital  role  in  the  care  of  these patients. Seventy five percent believed that their undergraduate programmes did not prepare them adequately to  cope with these patients in the community. However, their exposure to these patients improved their attitudes towards people with the syndrome. In conclusion although these young therapists started off being ill equipped, the exposure improved their ability to meet the challenges. This information is useful for curriculum development and transformation in physiotherapy.